Artificial Intelligence in Communication with Music Fans: An Example from South Korea - Marija Polak; Matilda KolicŚtanic\'; Marijana Togonal (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2022)
According to Kotler, Kartajaya, and Setiawan, there are five components of marketing 5.0: it is data-driven, predictive, contextual, augmented, and agile. This paper uses the case study method to investigate the presence of the 5.0 marketing components in promotional strategies employed by the South Korean popular music industry. The paper explores promotional strategies used by the BTS music group in particular. The group uses the 5.0 marketing method in its promotional strategies, especially in communication with the fans, and such communication thus enters the field of public relations. The case study analysis also indicates the use of data-driven marketing and predictive analytics, which are achieved using artificial intelligence. Additionally, elements of contextual marketing were used to improve the consumer experience, and augmented marketing was utilized to facilitate business, especially for front office staff. Finally, the analysis of BTS's promotional strategies shows a focus on innovation and flexibility, which are elements of agile marketing.
Keywords: D8; M3; O3; 330; marketing 5.0; strategies; communication; artificial intelligence; culture; music